Medical errors related with anaesthesia gas delivery equipment: Four cases for five years [Anestezi gaz daǧilim ekipmanlari ile i̇lgili hatalar: Beş yilda dört olgu] - (:unkn) unknown (My University, 2009)
Objective: Today technological development increases the reliability and the quality but cannot completely prevent the accidents related to anesthesia. In this case reports; we demonstrated the adverse anesthetic outcomes arising from anesthesia gas delivery equipment and to determine the origin of the error in order to elucidate the precaution about the reliable anesthesia practice. Material and Method: All the cases claimed to be the anesthesia malpractices sent to the Council of Forensic Medicine between 2003 and 2008 were investigated retrospectively. Four cases about misuse or failure of the anesthesia gas delivery equipment were included in this study. Results: Four of the 169 anesthesia malpractice cases were about adverse outcomes associated with gas delivery equipment. Its quite interesting to find, these 4 cases were all died and all of the medical management of these cases had errors. The nitrogen protokside misconnection is done with oxygen supplier, because of the unusual junction between the exiting points from the ceiling or the wall and the anesthesia equipment in the first three cases. On the other hand in two cases there's false colored tubes are chosen during the centralization process. In our 4th case, instrument check that has to be applied routinely before anesthesia had not been performed by the recently assigned anesthesia technician, circuit had not been closed because of insufficient knowledge of the instrument and this situation had been interpreted as "out of order" of the instrument. Discussion: We have to give continuous education about equipment standardization, standardized practice and providing reliable airway and oxygenation especially for emergency state in anesthesia practice, in order to prevent the adverse anesthetic outcomes related with the misuse or failure of the gas delivery equipment.
Keywords: Anesthesia; Equipment failure; Malpractice